Static Properties and Current-Driven Dynamics of Domain Walls in Perpendicular Magnetocrystalline Anisotropy Nanostrips with Rectangular Cross-Section - Eduardo Martinez (Advances in Condensed Matter Physics)
The current-induced domain wall motion along thin ferromagnetic strips with high perpendicular magnetocrystalline anisotropy is studied by means of full micromagnetic simulations and the extended one-dimensional model, taking into account thermal effects and edge roughness. A slow creep regime, where the motion is controlled by wall pinning and thermal activation, and a flow regime with linear variation of the DW velocity, are observed. In asymmetric stacks, where the Rashba spin-orbit field stabilizes the domain wall against turbulent transformations, the steady linear regime is extended to higher currents, leading to higher velocities than in single-layer or symmetric stacks. The pinning and depinning at and from a local constriction were also studied. The results indicate that engineering pinning sites in these strips provide an efficient pathway to achieve both high stability against thermal fluctuations and low-current depinning avoiding Joule heating. Finally, the current-driven dynamics of a pinned domain wall is examined, and both the direct and the alternating contributions to the induced voltage signal induced are characterized. It was confirmed that the direct contribution to the voltage signal can be linearly enhanced with the number of pinned walls, an observation which could be useful to develop domain-wall-based nano-oscillators.